Current methods for identifying plant hybrids: a case study of blackberry - I. Yu. Zhuravlev; M. T. Menkov; E. N. Markova; N. A. Dobarkina; A. Ya. Evlash; L. Yu. Shipilina; A. S. Rozanov (Труды по прикладной ботанике, генетике и селекции)
A review is presented on recent advancements in the identification of blackberry hybrids, including successful examples of using molecular markers and DNA barcoding for the classification of complex hybrid forms. Special attention is given to the comparative analysis of the effectiveness of such methods depending on the research objectives and resource availability.The review highlights the future need for standardizing methods and expanding genetic marker databases to improve the accuracy in the classification of blackberry hybrids.